Cognitive impairment - goodness of fit: Case report on intricacies in diagnosis (Journal of Psychiatrists' Association of Nepal, 2024)
Sporadic Creutzfeldt-Jakob disease (sCJD) is a rare neurodegenerative disorder characterized by rapid onset dementia and neurological symptoms, often challenging to differentiate from other neuropsychiatric conditions such as Wernicke-Korsakoff syndrome, especially in patients with alcohol dependence. We present a case of a 61-year-old female with a history of alcohol dependence, who initially presented with hallucinatory behaviour, memory impairment, and ataxic gait. Diagnostic evaluation revealed features reflecting Wernicke-Korsakoff syndrome on initial evaluation. However clinical profile, aided with MRI findings were suggestive of sCJD. The overlapping symptoms of sCJD and Wernicke-Korsakoff syndrome constitute a diagnostic dilemma, which gets further complicated with resource constraints for assessment. This case underscores the importance of enhancing our skills as clinicians in neurocognitive assessment to locate specific brain network dysfunction to conclude on a brain disorder, among cases presenting with neuropsychological symptoms.